High-Speed, Low-Power and Mid-IR Silicon Photonics Applications - Alloatti, Luca (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2013)
In this book, the first high-speed silicon-organic hybrid (SOH) modulator is demonstrated by exploiting a highly-nonlinear polymer cladding and a silicon waveguide. By using a liquid crystal cladding instead, an ultra-low power phase shifter is obtained. A third type of device is proposed for achieving three-wave mixing on the silicon-organic hybrid (SOH) platform. Finally, new physical constants which describe the optical absorption in charge accumulation/inversion layers in silicon are determined.